Original paperTelomere shortening in cultured human dermal fibroblasts is associated with acute photodamage induced by UVA irradiation - Yin, Bin; Jiang, Xian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Photoaging is the superposition of chronic ultraviolet (UV)-induced damage on intrinsic aging. Telomere length is a molecular marker of cell aging, and genomic instability due to telomere shortening has been linked to several aging-related diseases. Aim : To explore the effects of different doses of ultraviolet A (UVA) on the length of telomeres in human skin fibroblasts and partly reveal the mechanism of skin photoaging initiated by UVA irradiation. Material and methods: Primary cultured human skin fibroblasts were irradiated with different doses of UVA light. Cell viability, cell cycle phase, â-galactosidase, and the length of telomeres were assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, flow cytometry, cytochemical staining, and real-time polymerase chain reactions, respectively. Results : After UVA irradiation, inhibited proliferation, S phase accumulation and increased expression of senescence-associated â-galactosidase were observed in cultured fibroblasts. Moreover, the length of telomeres in UVA-treated cells was shortened in a dose-dependent manner as compared to controls (p < 0.05). Conclusions : These results suggest that telomere length in human dermal fibroblasts can be shortened by a single high dosage of UVA radiation, and that acute photodamage might contribute to early photoaging in human skin via rapid telomere shortening. This study potentially provides the basis for better understanding of the molecular mechanism of photoaging.